(untitled) (AACINI - International Journal of Industrial Engineering, 2024)
Currently, academic institutions of higher education are immersed in an innumerable number of academic-administrative processes such as student mobility, academic tutoring, professional practices, social service, and graduation, to name a few. Those processes are carried out routinely without taking the time to analyze them and see how they can be improved or made more efficient. On the other hand, the knowledge and experience of the people involved in its execution are not used, that is, the good practices that have been developed over time are not applied or the lessons learned that have allowed them to avoid mistakes are not known. In other words, the knowledge generated is not managed to ensure and improve the service received by the client (e.g. students, professors, directors, administrators, and/or people external to the institution), so when these processes are automated, only they go from being done manually to being executed through the support of information technology tools. From the above, the need to explore different approaches on how to analyze, improve and automate academic-administrative processes in higher education institutions is observed. The objective of this work is to propose a conceptual model with a knowledge management approach for the improvement and automation of academic-administrative processes that make their execution more efficient. As a result, a conceptual model composed of elements such as organizational environment, initial process, process executors, techniques and tools for process analysis, customer experiences, and information technology tools, to name a few, is proposed. It is intended that all these elements interact with each other with a knowledge management approach to ensure that the experience that the organization has in the execution of its processes leads them to offer a better service to its customers.